Hubungan Antara Presence Of Purpose Terhadap Career Indecision Making Pada Fresh Graduate Di Surabaya - Novitasari, Nimas Diana; Yuliawati, Livia (Psychopreneur Journal, 2019)
The purpose of this study was to investigate the relation between presence of purpose and career indecision making amoung fresh graduates in Surabaya. One of devolpmental tasks of youth is to find a career that aligns one’s potential. When fresh graduate can’t find one’s potential, they will experience career indecision making. Career indecision making cause, they don’t have presence of purpose.This study involve 107 respondens which graduated in 2015-2018. Measuring instrument for presence of purpose is unidimension scale of present of life from PWB and scale of present of life from Bundick and friends. And measuring instrument for career indecision making is scale from Germijs and De Boeck. Based on analysis results, there’s a relation between presence of purpose and career indecision making amoung fresh graduate in Surabaya.